KNOWLEDGE ABOUT BREASTFEEDING PRACTICES AMONG BREASTFEEFING MOTHERS IN WEST JAVA PRIANGAN - Ajeng Talitha Gandari; Insi Farisa Desy Arya; Dida Akhmad Gumida; Siti Nur Fatimah; Budi Sujatmiko (International Medical Journal Corp. Ltd, 2024)
Backgrounds: ASI is Breast milk is produced by the mother and contains all the nutrients needed by the baby for the growth and development needs of the baby. The breastfeeding recommendation recommended by WHO and UNICEF is to initiate early breastfeeding (IMD) one hour after birth, followed by exclusive breastfeeding for the first six months of birth and providing complementary foods until the age of 24 months. Lack of experience and knowledge of mothers about the importance of exclusive breastfeeding, there is no special care for the mother's breast in preparing for the birth of a child, so the baby's mother is more confident with formula milk.10 Lack of knowledge of mothers about exclusive breastfeeding and correct breastfeeding techniques will result in several problems for the mother such as sore nipples, swollen breasts, mastitis, or breast abscess. While the problem with babies is that babies often cry, which is interpreted by mothers and families that breast milk is not enough for babies. The purpose of this study was to describe the knowledge of breastfeeding mothers regarding breastfeeding in West Java Region IV Priangan. Methods: The research design is a descriptive method using a cross-sectional design. The data collection technique is primary data obtained through online questionnaires made through google forms. The research subjects were selected by taking non-probability sampling, namely purposive sampling. As forthe number of samples to be studied in this study was 384 samples. This research has been approvedby the Health Research Ethics Committee of Padjadjaran University. Results: The description of breastfeeding mother's knowledge is provenindicate the correct response to the knowledge description item. Most mothers have a good picture of knowledge about breastfeeding for babies. Both from the aspect of the benefits of breastfeeding for babies and mothers, to the factors that influence breastfeeding, the mother's knowledge is good in this regard. Conclusion: Overall, the description of mother's knowledge about breastfeeding in West Java is good. This is proven by the results of the answers from this study. This happens because the information that mothers get from social media and the surrounding community.